Experience the convenience of getting your questions answered at IDNLearn.com. Whether it's a simple query or a complex problem, our community has the answers you need.
Sagot :
To find the inverse of the function [tex]\( f(x) = \frac{x + 1}{x - 2} \)[/tex], we follow a series of steps. Let's denote the inverse function by [tex]\( f^{-1}(x) \)[/tex].
1. Express the function in terms of [tex]\( y \)[/tex] and [tex]\( x \)[/tex]:
[tex]\[ y = \frac{x + 1}{x - 2} \][/tex]
2. Swap [tex]\( y \)[/tex] and [tex]\( x \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ x = \frac{y + 1}{y - 2} \][/tex]
3. Solve for [tex]\( y \)[/tex]:
First, multiply both sides by [tex]\( y - 2 \)[/tex] to clear the fraction:
[tex]\[ x(y - 2) = y + 1 \][/tex]
Distribute the [tex]\( x \)[/tex]:
[tex]\[ xy - 2x = y + 1 \][/tex]
Move all terms involving [tex]\( y \)[/tex] to one side and the constant terms to the opposite side:
[tex]\[ xy - y = 2x + 1 \][/tex]
Factor out [tex]\( y \)[/tex] on the left side:
[tex]\[ y(x - 1) = 2x + 1 \][/tex]
4. Isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2x + 1}{x - 1} \][/tex]
Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \frac{2x + 1}{x - 1} \][/tex]
5. Compare with the provided options:
The correct answer is:
[tex]\[ f^{-1}(x) = \frac{2x + 1}{x - 1} \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{ f^{-1}(x)=\frac{2x+1}{x-1} } \][/tex]
This corresponds to the first option provided.
1. Express the function in terms of [tex]\( y \)[/tex] and [tex]\( x \)[/tex]:
[tex]\[ y = \frac{x + 1}{x - 2} \][/tex]
2. Swap [tex]\( y \)[/tex] and [tex]\( x \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ x = \frac{y + 1}{y - 2} \][/tex]
3. Solve for [tex]\( y \)[/tex]:
First, multiply both sides by [tex]\( y - 2 \)[/tex] to clear the fraction:
[tex]\[ x(y - 2) = y + 1 \][/tex]
Distribute the [tex]\( x \)[/tex]:
[tex]\[ xy - 2x = y + 1 \][/tex]
Move all terms involving [tex]\( y \)[/tex] to one side and the constant terms to the opposite side:
[tex]\[ xy - y = 2x + 1 \][/tex]
Factor out [tex]\( y \)[/tex] on the left side:
[tex]\[ y(x - 1) = 2x + 1 \][/tex]
4. Isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2x + 1}{x - 1} \][/tex]
Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \frac{2x + 1}{x - 1} \][/tex]
5. Compare with the provided options:
The correct answer is:
[tex]\[ f^{-1}(x) = \frac{2x + 1}{x - 1} \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{ f^{-1}(x)=\frac{2x+1}{x-1} } \][/tex]
This corresponds to the first option provided.
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. For dependable and accurate answers, visit IDNLearn.com. Thanks for visiting, and see you next time for more helpful information.